Nitrogen Use Efficiency and Yield of Maize under Deficit Irrigation - Abdenipour, M; Sarangi, A; RAJPUT, T B S; SINGH, MAN (Journal of Agricultural Engineering, 2012)
The NUE in maize (hybrid BIO-9681) crop with different levels of nitrogen under varying irrigation levels was estimated through an experiment conducted during 2009 and 2010. The field experiment comprised of four levels of irrigation and four levels of nitrogen application rates replicated thrice in a randomized complete block design. Irrigation water treatments in the main plots were: rainfed (W1); 50 % deficit irrigation (W2), 25 % deficit irrigation (W3) and full irrigation (W4). Nitrogen levels in sub plots were 0 (N1), 75 (N2), 150 (N3) and 225 (N4) kg.ha-1. Application of nitrogen significantly affected the grain yield and NUE for N2and N3 (75 and 150 kg N.haâ€1) treatments at 0.01 and 0.05 probability levels, respectively. However, the difference in yield and NUE were non-significant for N3 and N4 treatments. Maximum grain yield and biomass was observed for W4N4 treatment amounting to 6050 kg.ha-1 and 18650 kg.ha-1, respectively, during 2009. On the other hand, grain yield and biomass during 2010 was highest for W4N4 treatment amounting to 5860 kg.ha-1 and 18010 kg.ha-1, respectively. The highest NUE (19.6 kg grain.kgN-1) was obtained for W4N2 treatment combination during 2009, while it was highest (21.7 kg grain.kgN-1) for W3N2 treatment during 2010. Overall, the NUE decreased with increasing nitrogen level beyond 75 kg N.ha-1 (N2) at all irrigation levels.